Performance Analysis of 7075 Aluminum Alloy Strengthened by Cavitation Water Jet Peening at Different Scanning Speeds - Zijun Zhang; Yongfei Yang; Yong Gao; Gaowei Wang; Weidong Shi (Crystals, 2022)
Shot peening technologies can improve the performance of materials and extend the service life of parts. Cavitation water jet peening (CWJP) is a new shot peening technology that uses the shear effect of a high-speed jet in a submerged environment to produce a cluster of bubbles, thereby achieving a significant increase in impact performance. In this paper, CWJP was used to strengthen the surface of the 7075 aluminum alloy (Al7075), and the effects of CWJP with different scanning speeds on its microstructure and mechanical properties were investigated. The morphology evolution revealed that the plastic deformation of the sample surface became more serious and the surface roughness increased with the decrease in scanning speed. The distribution of residual stress and microhardness along the depth direction of the Al7075 was measured before and after the CWJP impact, and it was found that CWJP causes work hardening on the surface of the Al7075 and can convert the subsurface tensile stress of the Al7075 into compressive stress. The mechanism of grain refinement of the Al7075 during plastic deformation was systematically revealed. Therefore, CWJP can effectively improve the surface properties of the 7075 aluminum alloy.